Live Telecast of Judicial Proceedings as Means to Access to Justice in Nigeria: A Comparative Study - Ikubanni, Oluwaseye Oluwayomi; Adeboye, Oluwaseye Thompson; Titus, Joannah Emmanuel; Oyebanji, Aderemi Olubunmi (DiH: Jurnal Ilmu Hukum, 2025)
Any country's development, particularly that of its legal system, depends on having access to an open system of justice. The Nigerian justice system has been called weak, corrupt, and unreliable, which has made the public's mistrust of the court system worse. Thus, this paper interrogated the adoption of modern technology through live telecast of judicial proceedings as a means to access justice and restore the integrity of the Nigerian judiciary. It drew lessons from the UK, USA, South Africa, and India. The study used a doctrinal approach to legal research and a qualitative research methodology. The study found that the live telecast of court proceedings is constitutional when sections 36(3) and (4) are interpreted using a purposeful approach. Accordingly, the study came to the conclusion that live telecasts of court cases in Nigeria are possible. However, a few potential obstacles to its functioning in Nigeria include inadequate internet and power supplies, non-implementation of financial autonomy for the judiciary, absence of a specialized legal framework, and insufficient technological know-how of judicial personnel. The study made several recommendations, including giving the judiciary financial autonomy, passing particular legislation, enhancing internet and energy access, and providing judicial staff with ICT training.